2010
DOI: 10.1098/rspb.2010.0769
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in humans for assessing physical strength from the voice

Abstract: Recent research has shown that humans, like many other animals, have a specialization for assessing fighting ability from visual cues. Because it is probable that the voice contains cues of strength and formidability that are not available visually, we predicted that selection has also equipped humans with the ability to estimate physical strength from the voice. We found that subjects accurately assessed upper-body strength in voices taken from eight samples across four distinct populations and language group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
221
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(244 citation statements)
references
References 41 publications
14
221
8
Order By: Relevance
“…For example, lowering of F n and/or F 0 in dog barks increases attributions of the dog's aggressiveness in human listeners [20]. Playback studies with male deer vocalizations also show that male deer perceive the experimental lowering of F n and F 0 as more threatening ( [21]; see also [9,11,16,22,23] for more extensive reviews). Adult domestic dogs also correctly match the growls of larger versus smaller dogs onto visual cues of dog body size [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, lowering of F n and/or F 0 in dog barks increases attributions of the dog's aggressiveness in human listeners [20]. Playback studies with male deer vocalizations also show that male deer perceive the experimental lowering of F n and F 0 as more threatening ( [21]; see also [9,11,16,22,23] for more extensive reviews). Adult domestic dogs also correctly match the growls of larger versus smaller dogs onto visual cues of dog body size [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental evidence demonstrates that human adults are sensitive to these relationships, even within age and sex morphs [11,[16][17][18]. For instance, experimentally lowering F 0 and formant dispersion in young men's voices increases the speaker's perceived masculinity, size and age [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a posture that facilitates the assessment of body size can be considered as an index. Body size is a cue to physical strength (Sell et al 2010) and can be enhanced by an erect posture, like the one usually observed in the expression of pride (Tracy and Robins 2004). In this case, perceived body size is increased but within the limits offered by the actual size of legs and chest.…”
Section: The Reliability Of Social Signalsmentioning
confidence: 98%
“…We used a tailor's tape to measure the circumference of participants' right and left flexed biceps at the widest points (see Table 1 for descriptive statistics). Flexed biceps circumference and hand strength are strong predictors of upper body strength (Sell et al 2010); for example, flexed biceps circumference accounts for approximately 50 % of the variation in upper body lifting ability (Sell et al 2009). …”
Section: Physiological Measuresmentioning
confidence: 99%